Important HIV-associated conditions in HIV-infected infants and children - H. Rabie; B.J. Marais; R. van Toorn; P. Nourse; E.D. Nel; P. Goussard; N. Sellers; M.F. Cotton (South African Family Practice)
This article is the last in a series of 6 articles that discussed the management of HIV-infected children in a clinically orientated, practical and concise fashion. The topics covered previously include; 1) Preventing and diagnosing HIV-infection in infants and children, 2) Initiating anti-retroviral therapy in HIV-infected infants and children, 3) Maintaining HIV-infected infants and children on anti-retroviral therapy, 4) Common opportunistic infection in HIV-infected children: Part 1-respiratory infections and 5) Part 2 non-respiratory infections.